2022
DOI: 10.1002/jbt.23001
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazolium salts bearing the trifluoromethyl group as organofluorine compounds: Synthesis, characterization, crystal structure, in silico study, and inhibitory profiles against acetylcholinesterase and α‐glycosidase

Abstract: Here, we report the synthesis, characterization, and biological activities of a series of benzimidazolium salts bearing the trifluoromethylbenzyl group. All benzimidazolium salts were characterized by using nuclear magnetic resonance (NMR) ( 1 H NMR and 13 C NMR), Fourier transform-infrared spectroscopy, and elemental analysis techniques. The crystal structures of some of these compounds were obtained by the single-crystal X-ray diffraction method. Furthermore, the acetylcholinesterase (AChE) and α-glycosidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
2
7
1
Order By: Relevance
“…They showed benzimidazolium salts effectively inhibited AChE with K i s ranging from 0.94 to 10.24 μM. Tercan et al [46] . reported the synthesis and inhibition effect of benzimidazolium salts bearing the trifluoromethylbenzyl group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They showed benzimidazolium salts effectively inhibited AChE with K i s ranging from 0.94 to 10.24 μM. Tercan et al [46] . reported the synthesis and inhibition effect of benzimidazolium salts bearing the trifluoromethylbenzyl group.…”
Section: Resultsmentioning
confidence: 99%
“…They showed benzimidazolium salts effectively inhibited AChE with K i s ranging from 0.94 to 10.24 μM. Tercan et al [46] reported the synthesis and inhibition effect of benzimidazolium salts bearing the trifluoromethylbenzyl group. They found K i s in the range of 0.42 � 0.01 -1.27 � 0.16 μM for α-glycosidase and 1.36 � 0.34 -13.61 � 2.84 μM for AChE.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crude product was crystallized from ethyl alcohol/diethyl ether (1 : 3) at room temperature to afford the 3-benzyl-1-(3-cyanopropyl)benzimidazolium salt. [52] Yield: 85 % (0.708 g). m.p.…”
Section: Synthesis Of 3-benzyl-1-(3-cyanopropyl)benzimidazolium Bromi...mentioning
confidence: 99%